Hydrological variability affects particulate nitrogen and phosphorus in streams of the Northern Great Plains - K.J. Rattan (Journal of Hydrology: Regional Studies, 2019)
Study region: The study area is located in southern Manitoba, in the prairie region of Canada Study focus: This study examined the impact of hydrological variability on the timing and magnitude of nutrient export from seven agriculturally-dominated watersheds in the Red River Valley, Manitoba, Canada. New hydrological insights for the region: In 2013, discharge showed a seasonal pattern typical of streams traversing the Canadian prairies: high discharge during snowmelt followed by cessation of flow in early June due to lack of precipitation. In 2014, discharge still peaked during snowmelt but, compared to 2013, was 49% lower during snowmelt yet 21% higher during summer and fall due to greater rainfall. These hydrologic differences were associated with differences in fractionation of nutrients between years. Thus, higher concentrations and loads of particulate phosphorus (P) and nitrogen (N), and a greater (p < 0.05) share of the total nutrient pool in particulate forms (particularly for P), were observed during the snowmelt- dominated year (2013). Our findings show that the nutrient concentrations, fractionation and export from prairie watersheds differ between years, and amongst hydrological seasons, in relation to hydrological conditions. Additional management actions may be required to address changes in the quantity, timing and fractionation of nutrient export associated with rainier summers forecasted under future climate scenarios. Keywords: Nutrients, Hydroclimatology, Canadian prairies, Lake Winnipeg, Eutrophication